Application of Value Stream Mapping to Improve Service in The Departure Terminal at Halim Perdanakusumah Airport - Vita Sarasi; Ina Primiana; Desita Astira Kusnadiuthor (Universitas Mercu Buana, 2022)
This study aims to identify and reduce waste in the passenger flow process at the Halim Perdanakusuma Airport departure terminal, so that passenger service remains good even with limited terminal capacity. This research used a qualitative method with a case study approach. The method stages are the observation of the departure passenger flow process mapped through current state Value Stream Mapping (VSM), distribution of questionnaires to obtain critical waste with Borda analysis, and fishbone diagrams to find out the rooting causes of critical waste, the proposing process improvements, and the future state of VSM, The results showed that critical waste in the flow of departure passengers is 22.11%, which includes passenger activities waiting for the Security Check Point 1 and Point 2 queue. Furthermore, based on the current state of VSM, the lead time for departure passengers is 33 minutes 47 seconds and VAR is 20.22%. While form the future state of VSM, the lead time is 28 minutes 22 seconds with a VAR of 20.36%, resulting in time efficiency of 5 minutes 24 seconds.